Recurrent Infections and Cows-milk Hypersensitivity in a 2-Year-Old Girl with Hyper Immunoglobulin E Syndrome - Sonja Prcic; Jelena Tomić; Slobodanka Petrović; Anica Radulović; Verica Djuran; Zorica Gajinov (Iranian Journal of Allergy, Asthma and Immunology, 2011)
The hyperimmunoglobulin E  syndrome is a rare complex primary immunodeficiency characterized by high serum IgE levels, eczema, and recurrent infections. We present a case of 2-years-old girl with eczema and repeated bacterial skin and lung infections since the period of infancy. The patient also had eosinophilia, high serum levels of IgE, and cows-milk hypersensitivity. We describe the case, in order to illustrate the difficulty of establishing the diagnosis hyper-immunoglobulin E syndrome in a toddler.